Culture Matchmaking in Madurese Ethnic: A Study of the Motives, Factors and Impacts in Marriage Life - Herawati, Netty; Rohmah, Nailur (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Matchmaking is a culture that is still developing in Madura today. Where times are already modern, but this tradition occurs a lot among clerics or families who still have kinship. Over time, these matchmakings were submitted with culture, social and economic status. This article analyzes the motives, factors and their impact on marital life that causes it to remain accepted until now Methodology: This is phenomenology research. Primary data were collected through in-depth interviews and observations. The informants consisted of three Madurese ethnic matchmaking couples. Secondary data taken from his parents. Results: The results of the study show the motives of matchmaking: 1. not becoming a spinster, 2. Strengthening kinship 3. Establishing kinship with people who are already known, 4. Increasing social strata (if matchmaking with clerics), 6. Improving family economics, 7 Property / inheritance does not belong to others. Factors that affect matchmaking include: 1. economy, 2. culture, 3. Social status, 4. Kinship. The impact of matchmaking in the married life of Madurese ethnic couples consists of positive and negative impacts. Positive impacts are: 1. Accepting spousesincerely, 2. Not demanding, 3. Minim conflict, 4. Easier marriage adjustments.negative impacts are: 1. the family participates in regulating the household, 2. Infidelity. Applications/Originality/Value: Matchmaking based on these motives sound rational but curb the freedom to choose a partner by themselves. Matchmaking based on influencing factors and their impact on marital life teaches individuals to still maintain the values of submisive in Madura culture which is reflected in the proverb "buppa ’babbhu’ ghuruh ratoh"